Population-level morphological variation of Anisotremus interruptus (Gill, 1862) (Perciformes: Haemulidae) in the Tropical Eastern Pacific, with the description of two new species - Acevedo-Álvarez, Edgar Adrián; Ruiz-Campos, Gorgonio; Domínguez-Domínguez, Omar (Zootaxa, 2021)
The family Haemulidae is a wide-ranging group of marine fishes that are of significant commercial value in the Tropical Eastern Pacific (TEP). Phylogenetic studies on the species Anisotremus interruptus have revealed high levels of genetic diversity as well as divergence among populations in the TEP, which suggests that the taxonomic diversity of A. interruptus could be underestimated. Anisotremus interruptus has a large distribution, ranging from central Baja California, Mexico to northern Peru, including all oceanic islands except Clipperton. Recent genetic studies on this taxon indicate the presence of a species complex of at least three distinctive lineages. We performed a comparative study of the population-level meristic and morphometric variation of A. interruptus in the TEP to evaluate and identify possible morphological features concordant with the genetic differentiation of populations. Our results provide evidence of the presence of two new species of the genus Anisotremus, A. perezponcedeleoni sp. n. from the Revillagigedo Archipelago and A. espinozai sp.n. from Galapagos Archipelago-Cocos Island.